2009
DOI: 10.1098/rsbl.2009.0691
|View full text |Cite
|
Sign up to set email alerts
|

Group-foraging is not associated with longevity in North American birds

Abstract: Group-foraging is common in many animal taxa and is thought to offer protection against predators and greater foraging efficiency. Such benefits may have driven evolutionary transitions from solitary to group-foraging. Greater protection against predators and greater access to resources should reduce extrinsic sources of mortality and thus select for higher longevity according to life-history theory. I assessed the association between group-foraging and longevity in a sample of 421 North American birds. Taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
1
12
1
1
Order By: Relevance
“…Zonation allows the user to customize the analysis using a species weighting scheme. All prioritization schemes 5 2010, 2030, 2060, 2090-Winter RCP 4.5 2010, 2030, 2060, 2090-Summer RCP 8.5 2010, 2030, 2060, 2090-Winter RCP 8.5 2010, 2030, 2060, 2090-Scenario 2 Summer RCP 4.5 2010, 2030, 2060, 20902010, 2030, 2060, 2090Winter RCP 4.5 2010, 2030, 2060, 20902010, 2030, 2060, 2090Summer RCP 8.5 2010, 2030, 2060, 20902010, 2030, 2060, 2090Winter RCP 8.5 2010, 2030, 2060, 20902010, 2030, 2060, 2090 Note. Summer and winter prioritizations for each representative concentration pathway (RCP) scenario were combined into one landscape ranking using the highest rank across bot...…”
Section: Landscape Prioritizationsmentioning
confidence: 99%
“…Zonation allows the user to customize the analysis using a species weighting scheme. All prioritization schemes 5 2010, 2030, 2060, 2090-Winter RCP 4.5 2010, 2030, 2060, 2090-Summer RCP 8.5 2010, 2030, 2060, 2090-Winter RCP 8.5 2010, 2030, 2060, 2090-Scenario 2 Summer RCP 4.5 2010, 2030, 2060, 20902010, 2030, 2060, 2090Winter RCP 4.5 2010, 2030, 2060, 20902010, 2030, 2060, 2090Summer RCP 8.5 2010, 2030, 2060, 20902010, 2030, 2060, 2090Winter RCP 8.5 2010, 2030, 2060, 20902010, 2030, 2060, 2090 Note. Summer and winter prioritizations for each representative concentration pathway (RCP) scenario were combined into one landscape ranking using the highest rank across bot...…”
Section: Landscape Prioritizationsmentioning
confidence: 99%
“…We used maximum longevity as our dependent variable and 10 predictor variables. In addition to examining group size, we needed to account for additional variables that probably affect variation in longevity (Gaillard et al 1989;Blumstein & Møller 2008;Beauchamp 2010). For each species, we gathered data on: (i) median social group size, (ii) median adult body mass, (iii) median age at sexual maturity, (iv) mean monthly temperature, (v) mean monthly precipitation, (vi) mid-latitude (absolute values) of their range, (vii) mean human population density, (viii) degree of arboreality, (xi) longevity and (x) group-size sample size (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In comparative studies, Munshi-South & Wilkinson (2006) and Beauchamp (2010) found no relationship between group size and longevity in birds. Also, Blumstein & Møller (2008) found no relationship between the degree of cooperative care and cooperative breeding and lifespan in North American birds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum longevity can only be obtained from ring recoveries or resightings of known-aged birds. As such, estimates of maximum longevity will typically increase with the number of recoveries [20,21], which should be controlled to avoid potential biases. Nevertheless, the use of maximum longevity to estimate lifespan is controversial, and other sources of bias have been discussed [22], which makes such estimates not quite as reliable as adult annual survival rate.…”
Section: Introductionmentioning
confidence: 99%